2007
DOI: 10.1128/aac.01606-06
|View full text |Cite
|
Sign up to set email alerts
|

Modular Structure of Microcin H47 and Colicin V

Abstract: Microcins are gene-encoded peptide antibiotics produced by enterobacteria that act on strains of gramnegative bacteria. In this work, we concentrated on higher-molecular-mass microcins, i.e., those possessing 60 or more amino acids. They can be subdivided into unmodified and posttranslationally modified peptides. In both cases, they exhibit conserved C-terminal sequences that appear to be characteristic of each subgroup. In the hypothesis that these sequences could correspond to domains, gene fusions between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…We hypothesize that the MccL N-terminal sequence, which is quite different from the MccV one, is responsible for its specific antibiotic activity. This is in accordance with Azpiroz and Laviña (2), who showed that the specific toxicity of MccV and MccH47 was conferred by their N-terminal portions.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…We hypothesize that the MccL N-terminal sequence, which is quite different from the MccV one, is responsible for its specific antibiotic activity. This is in accordance with Azpiroz and Laviña (2), who showed that the specific toxicity of MccV and MccH47 was conferred by their N-terminal portions.…”
Section: Discussionsupporting
confidence: 76%
“…It was determined that a C-terminal domain of microcins E492, H47, and M was essential for the specific binding to FepA, Fiu, and Cir and possibly also for TonB-mediated import in the periplasm (4). Moreover, Azpiroz and Laviña (2) constructed chimeric peptides with exchanged C-terminal se- (57). However, we also observed that the exbB tolQ double mutant was not fully resistant to MccL, which suggests that another, unknown interaction and/or complementation exists.…”
Section: Discussionmentioning
confidence: 64%
“…In another study, chimeras of MccV and Microcin H47 (MccH47) were shown to be secreted from the MccH47 secretion machinery using either the MccV or MccH47 signal peptides [51]. It was believed that this capability was due to the similarity in transport proteins.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Azpiroz and Laviña constructed hybrid microcins fusing the N‐ and C‐terminal domains of MccV and MccH47. They arrived to the conclusion that the C‐terminal domains of these class II microcins are involved in the recognition of the OM receptor for the target cell uptake and the N‐terminal domain is the toxic region of the molecule [33]. Both, class IIa of LAB bacteriocin and class II of microcins must have an IM receptor binding region.…”
Section: Discussionmentioning
confidence: 99%